CONSUMERS' PREFERENCE OF RICE BRANDS IN KOREA (한국농촌경제연구원, 2009)
This paper conducts several analyses to discuss about consumers' preference of rice brands and suggest a way to reduce the number that currently stands at about 1,700 in the Korean market. With data collected from 358 survey respondents, a conjoint analysis was conducted to identify consumers' preferences of Korean rice in regard to such aspects as producing area, brand, category, and price. We particularly focused on analyzing the consumers' preference of rice brands, with some scenarios to decrease the number of brands. The paper also estimated the virtual market shares of rice brands. As results of the analyses, the paper shows that the grouping of individual rice brands in a city or county under one representative brand is the most preferred by Korean consumers. Even though the suggestion in this paper may not be acceptable to every case of rice brands in the Korean market, the findings might act as a guideline in developing a policy to cut down the number of Korean rice brands.
Keywords: Korean rice brands; conjoint analysis; virtual market share